Effects of parallel and perpendicular compressive stresses on the dielectric and ferroelectric properties of soft PZT ceramics - Unruan M. (2014)
Effects of compressive stress on the dielectric and ferroelectric properties of commercial soft PZT ceramics were investigated. The dielectric and ferroelectric properties were measured under compressive stress applied parallel and perpendicular to an electric field direction. The results showed that the dielectric properties; i.e. the dielectric constant (εr) and dielectric loss tangent (tan δ), and the ferroelectric characteristics; i.e. the area of ferroelectric hysteresis (P-E) loops, the maximum polarization (Pmax), the coercive field (E c) and the remanent polarization (Pr), changed significantly with increasing compressive stress. These changes depended greatly on direction of the applied stress. The stress clamping of domain wall, de-ageing and non-180° ferroelectric domain switching processes are responsible for the changes observed. In addition, a significant decrease in those parameters after a full cycle of stress application has been observed and attributed to the de-poling and stress-induced decrease in switchable part of spontaneous polarization at high stress. This study clearly showed that the applied stress has significant influence on the electrical properties of soft PZT ceramics. Copyright © 2010 Taylor & Francis Group, LLC.